A Real-Time Hooke's Law Experiment using IoT Mobile Application - Sudarmanto, Agus; Poernomo, Joko Budi; Suseno, Jatmiko Endro; Putranto, Ari Bawono; Basit, Muhammad Abdul (Diponegoro University Semarang Indonesia, 2026)
Hooke's Law is one of the topics in physics that can be simplified for better understanding through practical methods. This research aims to design a Real-Time remote Hooke's Law experiment in laboratory with Blynk as IoT Mobile Application, allowing students to experiment more flexibly in terms of time and location. The research methodology is based on Research and Development (R&D), including hardware design, software design, testing and data collection, data analysis, and report writing. This study resulted in the development of a laboratory Hooke's Law experiment and a Blynk application as its controller. The apparatus was tested by conducting experiments with three different loads: 30 grams, 40 grams, and 50 grams. The experiments aimed to obtain the spring constant, k, which were then processed using Hooke's Law formula based determine spring elongation data, ∆x. The 30 gram load yielded an average ∆x of 0.059 meters with an accuracy of 99.98% and an average k value of 4.90 N/m with an accuracy of 98.75%. The 40 gram load yielded an average ∆x of 0.059 meters with an accuracy of 99.93% and an average k value of 5.32 N/m with an accuracy of 95.40%. The 50 gram load yielded an average ∆x of 0.089 meters with an accuracy of 99.94% and an average k value of 5.53 N/m with an accuracy of 96.39%. The overall accuracy of the apparatus was 99.95% for ∆x and 96.18% for the spring constant. The system can choose the mass, m with control the stepper motor via mobile application and the result of research can be monitored in smartphone display such as such as spring elongation, ∆x, and spring constant, k as well as streaming video for monitoring purposes. [1] Arsada, Bakhtiyar, and B. Suprianto, “Ultrasonic Sensor Application for Distance Position Detection in Space Using Arduino Uno” State Univ. of Surabaya, 6(2), 137-145, (2017).[2] K. A. Gamage, D. I. Wijesuriya, S. Y. Ekanayake, A. E. Rennie, C. G. Lambert, and N. Gunawardhana,